2021
DOI: 10.1371/journal.pone.0256171
|View full text |Cite
|
Sign up to set email alerts
|

Pre-gestational diabetes: Maternal body mass index and gestational weight gain are associated with augmented umbilical venous flow, fetal liver perfusion, and thus birthweight

Abstract: Objectives To assess how maternal body mass index and gestational weight gain are related to on fetal venous liver flow and birthweight in pregnancies with pre-gestational diabetes mellitus. Methods In a longitudinal observational study, 49 women with pre-gestational diabetes mellitus were included for monthly assessments (gestational weeks 24–36). According to the Institute Of Medicine criteria, body mass index was categorized to underweight, normal, overweight, and obese, while gestational weight gain was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Finally, studies show that the liver plays a key role in fetal growth regulation and fat deposition. In pregnancies with pre-gestational diabetes, an increase in umbilical flow to the liver in combination with hyperglycemia augments fetal growth (35). Interestingly, even the small and thin Indian babies are relatively more adipose than English babies (36).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, studies show that the liver plays a key role in fetal growth regulation and fat deposition. In pregnancies with pre-gestational diabetes, an increase in umbilical flow to the liver in combination with hyperglycemia augments fetal growth (35). Interestingly, even the small and thin Indian babies are relatively more adipose than English babies (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, various biochemical substances in the blood play crucial roles as biological and chemical factors for foetal blood and nutrient acquisition, including vascular growth factors and blood sugar ( 32 , 33 ). Scholars from different countries have investigated the biochemical substances in foetal umbilical vein blood flow and concluded that multiple biochemical substances jointly affect foetal weight gain ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal liver dimensions are correlated with fetal size and weight, like other fetal biometric measurements, including biparietal diameter, head circumference, AC, and femur length. 16 In macrosomic fetuses, AC and therefore liver sizes are also large. The majority of the nutrient-rich blood carrying from the mother to the fetus through the umbilical vein in fetal life first comes to the liver.…”
Section: Discussionmentioning
confidence: 99%